Intranasal trivalent candidate vaccine induces strong mucosal and systemic immune responses against Neisseria gonorrhoeae - Lu, Qin; Yang, Hui; Peng, Yanfeng; Dong, Zeling; Nie, Pujing; Wang, Guangli; Luo, Shilu; Min, Xun; Huang, Jian; Huang, Meirong (Frontiers in Immunology, 2024)
The spread of multidrug-resistant strains of Neisseria gonorrhoeae poses a great challenge in gonorrhea treatment. At present, vaccination is the best strategy for gonorrhea control. However, given the extensive antigenic variability of N. gonorrhoeae, the effectiveness of monovalent vaccines is limited. Therefore, increasing the coverage of vaccination by using a multivalent vaccine may be more effective. In this study, a trivalent vaccine comprising three conserved antigens, namely, the App passenger domain, MetQ, and neisserial heparin binding antigen (NHBA), was constructed, and its protective effect was evaluated. Trivalent vaccines induced stronger circulating IgG and IgA antibody responses in mice than monovalent vaccines, in addition to eliciting Th1, Th2, and Th17 immune responses. Antiserum generated by the trivalent vaccine killed N. gonorrhoeae strains (homologous FA1090 and heterologous FA19), exhibiting superior bactericidal capacity than NHBA and MetQ vaccine antisera against N. gonorrhoeae, but similar capacities to those of the App vaccine antiserum. In addition, the trivalent vaccine antiserum achieved greater inhibition of N. gonorrhoeae FA1090 strain adherence to ME-180 cells compared to that elicited by the monovalent vaccine antiserum. In a mouse vaginal infection model, the trivalent vaccine was modestly effective (9.2% decrease in mean area under curve compared to the pCold-TF control mice), which was somewhat better than the protection seen with the monovalent vaccines. Our findings suggest that recombinant multivalent vaccines targeting N. gonorrhoeae exhibit advantages in protective efficacy compared to monovalent vaccines, and future research on multivalent vaccines should focus on optimizing different antigen combinations.